The dilemmas of statebuilding [ confronting the contradictions of postwar peace operations - Paris, Roland , 1967-; Sisk, Timothy D. , 1960- (Security and governance series, 2009)
Explores the contradictions that emerge in international statebuilding efforts in war-torn societies. This book argues that international efforts to construct effective, legitimate governmental structures in these countries are necessary but fraught with contradictions and vexing dilemmas. It draws on the research on postwar peace operations